THE EFFECT OF VIRGIN COCONUT OIL AGAINST SKIN TREATMENT OF LEPROSY PATIENTS - ZUHRIANA K YUSUF; NANANG R PARAMATA; WIRDA Y DULAHU (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Leprosy is a major cause of permanent disability among infectious diseases. The important parts of the human body that is disturbed in leprosy patients are the skin and peripheral nerves. Multidrug therapy treatment can kill leprosy germs, but previous existing defects cannot be eliminated. The purpose of this study was to determine the effectiveness of virgin coconut oil (VCO) in improving the skin of lepers. Methods: The methods of this research used a pre- and post-test of the control group of 50 people respondents which consisted of the treatment group of VCO and control group of original coconut oil. All treatment and control groups of respondents were given once per day for 1 month based on non-probability sampling. Results: The results showed that there was a significant effect of VCO on the skin of leprosy patients with a statistical value p=0.000 (α=0.001). This was also supported by the observation of the patient’s skin which all of patients experience changed in the results of the assessment of the skin after VCO administration intervention. This relates to lauric acid content in coconut oil which can reduce skin moisture levels. Conclusion: Based on the results of this study can be concluded that VCO is effective in improving the skin of lepers. VCO can be used as an alternative intervention in skin care for leprosy patients and to prevent further disability. Therefore, it is important for leprosy patients to obtain information about the use of VCO in the care and moisture of the skin.